Managing Software Development in Globally Distributed Teams. - Cusumano, Michael A. (Communications of the ACM, 2008)
This article presents information and advice on managing software development in globally distributed work teams. Discussed are the benefits of iterative software development techniques and the range of iterative software engineering practices, and creating an iterative contract with the customer. Article topics include the ongoing communication with the international teams, implementing time limits on modifications, and how to avoid misunderstanding between the requirements engineers, the programmers, and the testers.